2016
DOI: 10.1111/mms.12370
|View full text |Cite
|
Sign up to set email alerts
|

Dusky dolphin (Lagenorhynchus obscurus) social structure characterized by social fluidity and preferred companions

Abstract: Many coastal delphinids exhibit social structures with a high degree of fission‐fusion dynamics. However, little is known about fission‐fusion dynamics in semipelagic delphinids such as dusky dolphins (Lagenorhynchus obscurus). We analyzed dusky dolphin social structure in a winter foraging habitat in New Zealand. We examined the population‐level societal attributes of preferred/avoided companions, behaviorally specific preferred/avoided companions, and simple ratio (SR) association index strength and distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 89 publications
(193 reference statements)
0
13
0
Order By: Relevance
“…The final identifications of each individual dolphin in each sighting were verified by the lead researcher, who had the most photo‐id experience, as recommended by Pearson et al . (). The long‐term monitoring of this relatively small population, coupled with the high encounter rate, knowledge of life history, and well‐maintained photo‐id catalog of 204 known individuals (recorded between 2008 and 2016) greatly enhanced the process and efficiency of individual dolphin identification.…”
Section: Methodsmentioning
confidence: 97%
“…The final identifications of each individual dolphin in each sighting were verified by the lead researcher, who had the most photo‐id experience, as recommended by Pearson et al . (). The long‐term monitoring of this relatively small population, coupled with the high encounter rate, knowledge of life history, and well‐maintained photo‐id catalog of 204 known individuals (recorded between 2008 and 2016) greatly enhanced the process and efficiency of individual dolphin identification.…”
Section: Methodsmentioning
confidence: 97%
“…In Admiralty Bay a similar pattern was observed, but in addition to this social fluidity, Pearson et al . () found that some individuals were observed to form long term bonds throughout the entire study period. In our study, constant companions were not the preferred model; nevertheless Würsig and Bastida () reported that two dusky dolphins that were tagged together in the Península Valdés area in the 1970s were recaptured 780 km to the north seven years later.…”
Section: Discussionmentioning
confidence: 96%
“…In Admiralty Bay, New Zealand, dusky dolphins were observed to form preferred/avoided long‐term companions during all behavioral states (Pearson et al . ). Pearson () found that during foraging, the frequency of preferred associates was higher and the frequency of acquaintances was lower, indicating that foraging associates may “know” each other well.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations